Respect for Nature of Alas Kobong Folklore in Pacitan Regency and Relevance to Learning Literature in SMP Adiwiyata (Ecocriticism Studies) - Latifah Mutiara Sari; Sarwaji Surwandi; Sahid Teguh Widodo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to interpret ekokritik literary theory by expressing the value of environmental wisdom focused on respect for nature of fo Alas Kobong Folklore in Pacitan Regency. Ekokritik literature to examine the application of this folklore is through data classification based on the moral principles of environmental wisdom focused on respect for nature. The shape of this research is descriptive qualitative with an interactive approach to data sources transcript of interviews about Alas Kobong folklore of participants in Pacitan Regency. Data were collected through interviews, observation, documentation, field notes and transcriptions. There are three aspects of data analysis techniques, namely the description, analysis, and interpretation. The results of this study found five data contained in a respectful attitude towards nature which is included in the value of environmental wisdom of  Alas Kobong folklore in Pacitan Regency. In addition, the folklore of Alas Kobong can also implies learning literature junior secondary school Adiwiyata curriculum.